Gene Expression and Pharmacodynamic Changes in 1, 760 Systemic Lupus Erythematosus Patients From Two Phase III Trials of BAFF Blockade With Tabalumab. Issue 3 (27th February 2017) - Hoffman, Robert W.; Merrill, Joan T.; Alarcón‐Riquelme, Marta M. E.; Petri, Michelle; Dow, Ernst R.; Nantz, Eric; Nisenbaum, Laura K.; Schroeder, Krista M.; Komocsar, Wendy J.; Perumal, Narayanan B.; Linnik, Matthew D.; Airey, David C.; et al.
Abstract : Objective: To characterize baseline gene expression and pharmacodynamically induced changes in whole blood gene expression in 1, 760 systemic lupus erythematosus (SLE) patients from 2 phase III, 52‐week, randomized, placebo‐controlled, double‐blind studies in which patients were treated with the BAFF‐blocking IgG4 monoclonal antibody tabalumab. Methods: Patient samples were obtained from SLE patients from the ILLUMINATE‐1 and ILLUMINATE‐2 studies, and control samples were obtained from healthy donors. Blood was collected in Tempus tubes at baseline, week 16, and week 52. RNA was analyzed using Affymetrix Human Transcriptome Array 2.0 and NanoString. Results: At baseline, expression of the interferon (IFN) response gene was elevated in patients compared with controls, with 75% of patients being positive for this IFN response gene signature. There was, however, substantial heterogeneity of IFN response gene expression and complex relationships among gene networks. The IFN response gene signature was a predictor of time to disease flare, independent of anti–double‐stranded DNA (anti‐dsDNA) antibody and C3 and C4 levels, and overall disease activity. Pharmacodynamically induced changes in gene expression following tabalumab treatment were extensive, occurring predominantly in B cell–related and immunoglobulin genes, and were consistent with other pharmacodynamic changes including anti‐dsDNA antibody, C3, and immunoglobulin levels. Conclusion: SLE patients demonstrated increased expression of an IFN response gene signature (75% of patients had an elevated IFN response gene signature) at baseline in ILLUMINATE‐1 and ILLUMINATE‐2. Substantial heterogeneity of gene expression was detected among individual patients and in gene networks. The IFN response gene signature was an independent risk factor for future disease flares. Pharmacodynamic changes in gene expression were consistent with the mechanism of BAFF blockade by tabalumab.